Postoperative neuralgia in the leg after saphenous vein coronary artery bypass graft: a prospective study. Issue 1 (January 1988) - Nair, U R; Griffiths, G; Lawson, R A
Abstract : The degree of cutaneous sensory deficit in the leg was assessed after removal of the long saphenous vein in 50 consecutive patients undergoing coronary artery bypass vein grafts randomly assigned subcutaneous sutures or a single layer of sutures. Removal of the vein and repair of the leg incision were done by the same team of surgeons. In group 1 (25 patients) the leg incision was repaired with "00" Dexon subcutaneous and "00" prolene subcuticular sutures while in group 2 (25 patients) closure was effected by a single layer of interrupted "00" nylon sutures. All had crepe pressure bandage from the base of the toes to the groin for the first 24 hours followed by TED stockings for six to eight weeks. Sutures were removed on the eighth postoperative day. Cutaneous sensation in the leg and ankle was assessed 48 hours, seven days, and six to eight weeks after surgery, and a final comparison of the cosmetic effects and sensory perception after one year or more was made in 37 patients. There were no major differences between the groups at 48 hours in sensory abnormalities (anaesthesia, hyperaesthesia, and pain) but sensory recovery was significantly better in group 2 at the second and third assessments. There was some reduction in sensory abnormalities at the final review in group 1. No appreciable difference was noted in the quality of the scar between the two groups. We conclude that cutaneous sensation is better preserved by repairing the leg incision in a single layer. Subcutaneous sutures may produce neuropraxia of the long saphenous nerve by direct pressure as healing progresses.